تصميم مركز شبابي ثقافي ترفيهي اجتماعي (بيت الشباب) - بدر, جنى; القواسمة, ختام (جامعة بوليتكنك فلسطين, كلية الهندسة , معماري, 2018)
فـي ظـل الظروف الصـعبة التـي يعيشـيا الشـعب اليمسـطيني, والتـي يتقـدمها الحصـار الاسـرائيلي , واثـره علـى شـتى مجـالات الحياة في فلسطين و ما تسبب به من انتشار العديد من المشاكل الاجتماعية و البطالة , مما ادى الى محاربـة المجتمـع فكريـا وثقافيـا ورياضـيا , ومـن هنـا يـاتي دور المعماري لاعادة احياء هذه الثقافات من خلال انشاء مراكز شبابية متكاملة فـي تنميـة المجتمـع فـي شـتى المجـالات, فقمنـا بتحليـل المشـاكل لتحديـد المحـاور التـي سـيتم العمــل عليها , فبـدأنا بالجانـب الاجتمـاعي والتعـرف علـى فئـة الشـباب كفئـة مسـتهدفة فـي المشـروع ومـن ثـم التعـرف علـى دور الشـباب فـي التنميـة , ومـن خـلال الحـالات الدراسـية تـم اسـتنتاج بعـض المعـايير التصـميمية والتخطيطية الخاصة بالمراكز الشبابية والتـي سـيتم اعتمادهـا فـي المشـروع , وبعـد اجـراء مقـابلات شخصـية مـع احـد المسـؤولين فـي المركز الكوري وبلدية الخليل وتحليل نتائج الاستبيان قمنا بعمل جدول برنامج المشروع ووصفه بشكل اوسع وتحديد بعض العلاقـات والانشطة داخل المشروع ومعرفة المشاكل المتواجدة للعمل على حلها . مـن خلال مـا سـبق ذكـره ,تتضح هنا المحـاور الاساسـية لمشـكلة البحـث والتـي سـيتم العمـل عليهـا , مـن الجوانـب الرياضـية الاجتماعيــة و الثقافيــة , فاقترحنــا فــي بحثنــا هــذا اقامــة مركــز شــبابي متكامــل يشــمل جميــع النــواحي الرياضــية الثقافيــة التعليميــة و الاجتماعية وتم تحديد قطعة الارض بناءا على معايير سيتم شرحها فـي الفصول القادمة مع توضيح لعناصر المشروع المقترح As an occupied land, Palestine suffers from various issues and everyday life problems, of which are the unemployment high rates among youth; this resulted in an unhealthy environment and society that undergoes cultural and intellectual troubles. Here lies the role of an architect to do his best to create, develop and maintain a healthier life style by building a new complete youth center to be the avenue to all young adults, a center where they can find a solace for their empty free lives. We started by understanding and studying the role of young adults in society from different aspects and how they can develop a more advanced society for themselves. And from our forms of study and surveys we concluded the standards of designing and planning an innovative youth center that will be applied in our project. After meeting with a board member of the football association and municipality of Hebron, and recording surveys results, we did finalize the project’s plan in a wider more detailed manner and point out different complications that we need to find a solution for and work on right away. As mentioned above, we clearly see the standards of a case study that tries to develop a more cultural, intellectual and active society for youth. Our solution comes as a center that can be built to absorb and perpetuate the lives of young adults willing to live a more active life; in a piece of land that was selected based on a set of standards to be discussed later within the details of this project.
, cd , no of pages 97, معماري 7/2018 , in the store
Keywords: معماري , مركز ثقافي , اجتماعي , ترفيهي , الشباب